Controlling Smart Home Appliances using Raspberry pi - et. al., Konagalla Pallavi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has become an integral part of human life continuously making daily tasks easier. marketing has been under the influence of the Internet of Things in more ways than we expected. IoT technology or Internet of Things can be a network of objects that can transmit data to audiences without human connections, such as smart devices, electronics, and devices. Various IoT applications can be made using open hardware-related hardware. During this study Anomaly prevention is done by creating the only BOT of authorized users in the telegram app. In the event of any abnormal behavior it is usually observed using a camera.